Exploratory Research Regarding the Adoption of Disruptive Technologies Before and During the Pandemic Crisis: A Comparative Case Study - Ana-Maria NEDELCU; Daniela ZAMFIR; Cristinel BĂLAN; Monica-Lavinia DAN; Andra-Luisa PREDA (Communications of International Proceedings, 2021)
4IR has led to the digitalization of vital economy sectors such as healthcare, agriculture and industry. This was possible due to the interconnected disruptive technologies that were brought with the emergence of 4IR, most of them being AI-dependent. The main goal of the Digital Revolution (4IR) is to create Smart Factories, representing a new, flexible way of production with the aid of digital technologies such as automation, robotization and artificial intelligence. Market players were always interested in finding new alternatives of making their products innovative and competitive on the market and now they find themselves even more constrained by the globalization and liberation of international trade to keep their products sustainable and worthy of profit. The global market competitivity has increased the need for digitalizing the production due to the larger consumer demand and faster product delivery. In this paper we have conducted a comparative analysis at the global and regional levels in what concerns the adoption of emerging technologies in the pre- and during the pandemic period.
Keywords: Industry 4.0; Disruptive Technologies; Comparative Analysis; Pandemic.